Optimizing Soft Tissue Emergence Profile Around One-Piece Dental Implants - Abduljaleel Azad Samad (Erbil Dental Journal)
Background and Objective: One-piece implants were introduced many years ago, however, in the last years, they have gained acceptance as a therapeutic alternative for many clinical cases. The soft tissue surrounding the neck of one-piece implants, particularly in the esthetic zone, is a cause for concern despite the clinical effectiveness of these implants. The purpose of this study is to propose a simple way for optimizing soft tissue around one-piece dental implants.